Influence of head rotation on ease of mask ventilation: a randomized crossover study - Ravula, Ramakrishna; Tappa, Rabbani; Jonnavithula, Nirmala (International Journal of Research in Medical Sciences, 2023)
Background: Mask ventilation is an essential part of airway management. Head rotation increases the cross-sectional area of upper airway and improves upper airway patency. Methods: A prospective crossover study in 40 patients aged 18-69, ASA physical status I, II, III and who needed general anesthesia with tracheal intubation were selected, divided into two groups of 20 each, group I and Group II. When apnea was achieved after standard general anaesthesia, mask ventilation was performed using pressure-controlled ventilation, peak inspiratory pressure 15 cm of water, 10 breaths per minute, I:E ratio 1:2. Face mask held by two hands. Group I patients received mask ventilation with the head in a neutral position for one minute, after which the head was turned to the right for one minute and the head is returned to the neutral position for one minute. In group II patients, mask ventilation was performed from right lateral position to neutral position to right lateral position. In each position, airway pressure, compliance and expiratory tidal volume were measured. Results: There was no statistically significant difference between groups with respect to demographic data. The mean expiratory tidal volume was high in head rotation than neutral position (469.545±120.09 ml vs. 397.815±86.03 ml) p value <0.05. A statistically significant (p value=0.045) seen with respect to compliance which was slightly higher in head rotation (35.83) than neutral position (29.31). Conclusions: Head rotation to the lateral position increases the expiratory tidal volume and compliance significantly as compared to head in neutral position and improves mask ventilation after induction of anaesthesia.